Pelatihan dan Pengembangan Pusat Informasi Konseling Remaja (PIK-R) guna Optimalisasi Kesehatan Reproduksi Remaja Di Kelurahan Togafo Kota Ternate Barat Tahun 2022 - Nuzliati T Djama; Nurdiana Lante (Poltekkes Kemenkes Kendari, 2022)
The Community Service Partner is the Manager of the Youth Counseling Information Center (PIK-R) Togafo Village, West Ternate City. Adolescents are vulnerable to health problems because of physical development, maturation of sexual and psychosocial organs that can affect adolescent behavior, supported by minimal understanding or knowledge, they will be very vulnerable to causing adolescent problems in society. Preliminary data in the Togafo Sub-district showed that the facilities in the form of the PIK-R room were already available, but there were no youth education innovation activities except for the posyandu service by the puskesmas, which was held once a month. Regarding adolescent reproductive health problems, data was obtained that there were still cases of early marriage, anemia in adolescent girls, and there was still drug abuse of the glue type. The solutions to improve competence and prevent adolescent health problems are: 1) Optimizing PIK-R through socialization of the PIK-R function for coaches and managers, 2) Implementing Peer Adolescent/Peer Counselor training, 3) Developing PIK-R programs through service websites Online adolescent reproductive health with the brand